Pendampingan Masyarakat dalam Pendataan Aset Infrastruktur Jalan Desa - Kasmir Gon; Patrisius Valdoni Sandi (Unika Santu Paulus Ruteng, 2024)
Golo Tolang Village in NTT Province is a PkM partner because it has problems in administering village road infrastructure, namely limited knowledge and ability of village government administrators to collect data on village road infrastructure assets. This problem resulted in the findings of the 2022 East Manggarai Regency Inspectorate's inspection, where village funds were allocated to assets that did not yet have legal status. This PkM is implemented with the aim of increasing the knowledge and capabilities of village government administrators in terms of data collection on village road infrastructure assets and the availability of data on village road infrastructure assets in Golo Tolang Village as material for proposals to the regent to determine their status as village roads. The method applied in this PkM is socialization and assistance in filling out the format based on Minister of Home Affairs Regulation Number 1 of 2016, attended by 16 participants. Stage 1 evaluation obtained a score of 75, stage 2 evaluation obtained a score of 93.75, and stage 3 evaluation obtained a score of 100. Finally, a draft of the proposed village road infrastructure assets in Golo Tolang Village was obtained, totaling 41 sections with a total length of 125.03 kilometers to determine its status as a village road in accordance with the provisions of the applicable regulations